Terrorism and Business - Bruno S. Frey (Center for Research in Economics, Management and the Arts (CREMA), 2007)
Deterrence has been a crucial element in fighting terrorism, both in politics and in rational choice analyses of terrorism. However, there are two strategies that are superior to deterrence. The first one is to make terrorist attacks less devastating and less attractive to terrorists through decentralization. The second one is to raise the opportunity cost - rather than the material cost - for terrorists. These alternative strategies will effectively dissuade potential terrorists. It is here argued that they not only apply to society as a whole but can also usefully be applied by business enterprises.
Keywords: D74; H56; K42; 330; Terrorism; Deterrence; Decentralization; Opportunity Cost; Business; Enterprises